Product strategy and management - Baker, Michael J. (Henry Stewart Talks, 2012)
Competition, Demand and supply, Product management and the PLC, The growth vector matrix, The concept of product portfolios, The BCG growth vector matrix, Assessing the contribution of individual products, Criticisms of portfolio analysis, Managing the product through its lifecycle